Teacher's Strategy in Forming Social Attitudes of SD Negeri 36 Students in Banda Aceh - Ilmi, Muhammad Ridhaul; Ahadin, Ahadin; Sulaiaman, Sulaiman (Elementary Education Research, 2023)
The aim of the research was to describe the teacher's way of building the social attitudes of SD Negeri 36 Banda Aceh students. The research used a qualitative approach and the type is descriptive. 6 homeroom teachers at SD Negeri 36 Banda Aceh were considered as research subjects. Then the data in this study were collected through observation and interviews. The data is then analyzed using data reduction, data presentation and conclusion. From the results of the study it was found that social attitudes could be developed by SD Negeri 36 Banda Aceh teachers including honest, disciplined, responsible, polite, caring and confident attitudes. The developed social attitude has been almost evenly distributed with the pattern of application and exemplification. The teacher's strategy in taking action to build students' social attitudes is through the application of exemplary strategies, group work, habituation of religious values and giving rewards. From the results of the study it can be concluded that the strategies used by the teacher in shaping the social attitudes of SD Negeri 36 Banda Aceh students are exemplary, group work, habituation of religious values and determination of consequences. The strategy used is able to support students to build social attitudes, especially honest, disciplined, responsible, polite, caring and confident attitudes.